Decentralization as a strategy for redemocratization in the Philippine political system - De Guzman, Raul P. (1988)
The Aquino government has the responsibility of giving more meaning to decentralization, or systematically and rationally dispersing government power and authority to local level institutions so as to allow multi-sectoral decision making to be as close as possible to the spatial location of the problem. Decentralization can be undertaken by way of deconcentration, devolution, privatization, and through the use of alternative channels for delivering services, primarily through non-governmental organizations (NGOs). For decentralization to be meaningful, 1) the selection process of leadership at local levels must truly reflect the genuine will of the constituency; 2) the problems of duality of government services at the field level must be resolved; 3) more power and responsibilities should be entrusted to the local government; 4) the government must pursue the policy of effective privatization; 5) the increasing uses of NGOs must be considered; and 6) the government must continue in its advocacy of transparency in its operations.
Keywords: Decentralization in government; Democracy; Philippines -- Politics and government